Impact of rituximab on stem cell mobilization following ACVBP regimen in poor‐risk patients with diffuse large B‐cell lymphoma: results from a large cohort of patients. Issue 1 (7th May 2012) - Lefrère, François; Bastit‐Barrau, Dominique; Hequet, Olivier; Bourin, Philippe; Mathieu‐Nafissi, Suzanne; Bohbot, Alain; Tilly, Hervé; Salles, Gilles; Fermé, Christophe; Lapierre, Valérie; Fornecker, Luc; Micléa, Jean‐Michel; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND: The ACVBP regimen is an efficient induction regimen for poor‐risk patients with diffuse large B‐cell lymphoma (DLBCL) before consolidative autologous stem cell transplantation. Adjunction of the monoclonal anti‐CD20 antibody rituximab (R‐ACVBP) was recently found to be superior to ACVBP alone. This study assessed the impact of rituximab on stem cell mobilization in two similar consecutive groups of patients treated with ACVBP in two prospective, controlled trials. STUDY DESIGN AND METHODS: The first trial (LNH‐98B‐3) involved 137 patients treated with ACVBP alone. In the second trial (LNH‐03‐3B), 91 patients received an R‐ACVBP regimen. Stem cell mobilization was performed after a course of (R)‐ACVBP. RESULTS: The median peak numbers of blood CD34+ cell counts recorded before the first apheresis procedure in the ACVBP and R‐ACVBP groups were 69 × 106 and 63 × 106/L, respectively (p = 0.55). The median numbers of CD34+ cells collected were 7.1 × 106 and 6.0 × 106 CD34+ cells/kg for the ACVBP and R‐ACVBP groups, respectively (p = 0.13). The median number of apheresis procedures required for gathering the minimum amount of CD34+ cells (2 × 106/kg) was the same in the two groups. CONCLUSION: When compared with ACVBP alone, adjunction of rituximab does not impair stem cell mobilization.